The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1080/13600801003743364
|View full text |Cite
|
Sign up to set email alerts
|

Managing and resourcing a program of social integration initiatives for international university students: what are the benefits?

Abstract: There has been much concern in the higher education sector recently about the well-being and the safety of slightly more than 200,000 international students studying in higher education in Australia. In recognition of the economic and socio-cultural value of the international student cohort, as well as the significant challenge and risk of studying away from family and friends in a foreign community, CQUniversity has focused for the last two years on improving social integration for over 5000 international stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…Most importantly, activities must centre on the enhancement of intercultural skills and social integration. These can best be achieved through broader institutional policy and strategies such as internationalising the curriculum (Leask, 2001), the inclusion of intercultural outcomes for all students (Campbell, 2010;Leask, 2004), and the development of mandatory intercultural mediation and social integration practices (Owens & Loomes, 2010) for all students, both domestic and international. Cultural mentoring, intercultural mediation programmes and the sharing of cultural knowledge have all been found to assist international students in making gains in intercultural interaction and adaptation (Pedersen, 2010).…”
Section: Implications For Internationalisation Policy and Managementmentioning
confidence: 99%
“…Most importantly, activities must centre on the enhancement of intercultural skills and social integration. These can best be achieved through broader institutional policy and strategies such as internationalising the curriculum (Leask, 2001), the inclusion of intercultural outcomes for all students (Campbell, 2010;Leask, 2004), and the development of mandatory intercultural mediation and social integration practices (Owens & Loomes, 2010) for all students, both domestic and international. Cultural mentoring, intercultural mediation programmes and the sharing of cultural knowledge have all been found to assist international students in making gains in intercultural interaction and adaptation (Pedersen, 2010).…”
Section: Implications For Internationalisation Policy and Managementmentioning
confidence: 99%
“…The international evening was highly praised, as students could bring their families, wear their national dress and offer samples of typical dishes from their country. A study of Australian universities by Owens and Loomes (2010) highlighted how much international students appreciated social activities which enabled them to mix with staff and students. The study not only provided evidence that social activities improved students' well-being and satisfaction but also that academic performance was enhanced.…”
Section: A Benefits Of the Schemementioning
confidence: 99%
“…As the discussion of the reviewed studies shows, researchers have identified academic, social, and personal factors that affect international student experience in American colleges and universities. Building on theoretical frameworks of student involvement (Astin, 1984(Astin, , 1993, college student development and student engagement (Pascarella, 1985;Pascarella & Terenzini, 2005), and student integration (Tinto, 1993), researchers have linked international college student outcomes to levels of academic and social engagement with various groups on campus including faculty, peers, administrators, and staff (Andrade, 2008;Kwon, 2009;Owens & Loomes, 2010;Sherry et al, 2010;Zhao et al, 2005). Academic engagement of international students is often viewed and discussed as part of student engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The study findings suggest that program participants compared to nonparticipants developed more social connections with domestic students and eventually were better adjusted to life on campus, which was linked to better overall college experience. Kim and Egan (2011) and Owens and Loomes (2010) also stressed the importance of peer interaction and the value of programs supporting social integration between domestic and international students. Kim and Egan conducted an exploratory case study of a formal crosscultural mentoring program at a large American university.…”
Section: Trends In Research On International Studentsmentioning
confidence: 99%
See 1 more Smart Citation